2016
DOI: 10.1128/jcm.00439-16
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anti-Hepatitis B Virus Drug Resistance Mutations Based on Multicolor Melting Curve Analysis

Abstract: Detection of anti-hepatitis B virus (HBV) drug resistance mutations is critical for therapeutic decisions for chronic hepatitis B virus infection.We describe a real-time PCR-based assay using multicolor melting curve analysis (MMCA) that could accurately detect 24 HBV nucleotide mutations at 10 amino acid positions in the reverse transcriptase region of the HBV polymerase gene. The two-reaction assay had a limit of detection of 5 copies per reaction and could detect a minor mutant population (5% of the total p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Real-time PCR reduces the risk of contamination due to its applicability and speed. Therefore, it is widely used to detect drug resistance mutations ( Mou et al 2016 ).…”
Section: Molecular Assaysmentioning
confidence: 99%
“…Real-time PCR reduces the risk of contamination due to its applicability and speed. Therefore, it is widely used to detect drug resistance mutations ( Mou et al 2016 ).…”
Section: Molecular Assaysmentioning
confidence: 99%
“…Recent studies have shown that the TaqMan probes can be used not only for monitoring PCR in real time but also for melting curve analysis under asymmetric PCR conditions (Huang et al, 2011). Multicolor melting curve analysis using the TaqMan probe has been successfully applied in mutant gene detection and genotyping (Botezatu et al, 2017;Mou et al, 2016;Wang et al, 2017;Xia et al, 2016;Huang et al, 2016;Gao et al, 2015;Huang et al, 2017). Nevertheless, the application to multiple virus detection has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%